PENGARUH MEDIA BIG BOOK TERHADAP KEMAMPUAN MENULIS SISWA KELAS I PADA PEMBELAJARAN BAHASA INDONESIA - Qorry Wulan Desnia; Sugiaryo Sugiaryo; Elinda Rizkasari (Widya Wacana: Jurnal Ilmiah, 2023)
The purpose of this reseach is to find out whether there is an influence of Indonesian language learning media on grade I students at Joglo Elementary School No. 76 Surakarta in the 2022/2023 academic year. This reseach is a quantitative reseach with a quasi-experimental design. The reseach sample is 27 student in class IA and 26 student in class IB. before being used for reseach instruments, validity tests were requested by experts in their field. Data collection techniques namely tests, observations, interviews, and documentation. Based on the result of data analysis the Big Book media has an effect on the writing ability of grade I students at Joglo Elementary School No. 76 Surakarta in Indonesia language subjects. See from the hypothesis test result tcount 4,382 with (df) 51 and a significance level of 0,05, when compared to ttable 1,675 is grater 4,382 > 1,675, therefore Ho is rejected and Ha is accepted. It can be concluded that the use of Big Book media has an effect on the writing ability of students in grade I at Joglo Elementary School No. 76 Surakarta in ethe 2022/2023 academic yearKeywords: Big Book Media, Writing Ability